Impact of The Covid -19 Pandemic on Mental Health in Society - Any Sulistyaningsih (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Another health problem that has emerged as a result of the Covid-19 pandemic is mental health problems which if left unchecked can develop into serious health problems. The Oxford study shows that people over the age of 50 who are female, and those who are hospitalized due to the coronavirus are much more likely to suffer from brain and psychological complications, a much higher risk of dementia, a brain disorder condition, in Covid-19 survivors. 19. The research method used is descriptive qualitative research. The Covid-19 pandemic not only has an impact on physical health but also has an impact on other aspects of life such as the social and economic aspects of the community. From the results of interviews with the subject, the author indicates that individuals infected with Covid-19 experience anxiety, worry, and fear, even stress. Anxiety is not only due to the coronavirus infection but also the social environment in which they live which still discriminates against patients and their families infected with Covid-19.